"Estoy Explorando Science": Emergent bilingual students problematizing electrical phenomena through translanguaging. Issue 5 (19th June 2020) - Suárez, Enrique
Abstract: As science education continues to embrace science‐as‐practice, equitable science learning environments must value and leverage emergent bilingual students' ways of communicating. This study investigates the translanguaging practices of a group of elementary‐aged emergent bilingual students while they problematized electrical phenomena. Building on asset‐oriented theories for supporting student learning, I utilize translanguaging as a theoretical and pedagogical lens for understanding how emergent bilingual students leverage their full semiotic repertoires for productive disciplinary engagement. The study took place in an out‐of‐school program focused on creating opportunities for students to problematize electrical phenomena, specifically electrical resistance. I present a close analysis of students constructing models of electric flow through a circuit and how electrical resistance regulates that flow. The findings also include evidence that students engaged in different kinds of translanguaging practices when problematizing electrical phenomena and co‐constructing knowledge with each other and the instructor. Specifically, students drew from and used multiple linguistic and nonlinguistic semiotic resources for communicating their models. Finally, the findings suggest that the instructor's pedagogical moves and own translanguaging practices implicitly signaled to students when and how to participate in translanguaging practices themselves. The findings emphasize the importance of desettling what counts as productive forms of communication in science for elementary‐aged emergent bilingual students by eschewing pedagogical models that police discursive boundaries. Therefore, equitable science learning environments must create opportunities for emergent bilingual students to leverage their full semiotic repertoires for meaning‐making, by inviting and valuing multiple languages and gestures.